Identify virtual ligand hits using consensus scoring approach for drug target S. Aureus - Bharath Siva Varma, P; Yesubabu, Adimulam; Subrahmanyam, K (International Journal of Engineering and Technology, 2018)
The associations amongst protein and ligand can be assessed for scoring functions based on the binding modes of ligand obtained from search algorithms. Several scoring functions have been proposed and every method has their own strengths and weaknesses, hence a multiple scoring analysis referred as consensus scoring increases the overall signal noise ratio. Therefore, top ten ligands obtained and were subjected to re-scoring using mcule, AutoDock and X-score functions. A computational consensus scoring analysis was taken up for a dataset of top ten PubChem compounds which are identified to exhibit better inhibitory properties against phosphotransacetylase, a putative drug target for S. aureus.